Association of Mastalgia with Anxiety, Depression and Quality of Life in Adolescent Females - Deen, Qaim; Nadeem, Muhammad; Ahmad, Muhammad; Shabbir, Faisal; Moeen ud din, Muhammad Bilal (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: For the association of mastalgia with anxiety, depression and quality of life in adolescent females. Methodology: Cross-sectional prospective study was conducted in the Department of Surgery Special Unit, Services Hospital, Lahore and Department of Surgery, Hayat Memorial Hospital Lahore from 1st November 2022 to 30th April 2023.Fifty mastalgia patients after complete clinical diagnosis and confirmation of mastalgia (non-cyclic) and also 50 controls were enrolled. All adolescent females within the age group of 20-40 years were selected. Those adolescent females having no clinical history of breast disease or psychiatric illness were taken through volunteer approach as controls. All clinical information of patients and controls as well as the one related with qualitative variables were entered in a well-structured questionnaire. Results: The mean age of the mastalagia patients was 27.23 ± 4.20 years while that of controls was 26.62 ± 4.53 years having no comparative difference between the two groups in accordance with the mean age. There was a significant variance within energy levels of both groups with an obvious reduction in the energy level of the mastalgia group in comparison to the health controls. Hamilton-Depression Scale (HDS), and Hamilton Anxiety Rating Scale (HARS) scoring method also presented a significant variance between females suffering from mastalgia in comparison to the normal control females. Practical Implication: Mastalgia, or breast pain, significantly impacts patients' physical, general, and psychological health. It impairs physical functioning, reduces energy levels, and leads to depression and anxiety. A holistic approach, addressing both physical symptoms and psychological impacts, is crucial for improving patients' quality of life and promoting overall well-being. Conclusion: Mastalgia has a significant impact on physical functioning, generalized health, body aching and psychological health